Progress of equalizing basic public health services in Southwest China--- health education delivery in primary healthcare sectors - Rui Zhang; Yong Chen; Shili Liu; Shengxiang Liang; Geng Wang; Li Li; Xingneng Luo; Ying Li (BMC, 2020)
Abstract Background Equalizing basic public health services (BPHS) for all has been one goal of the health system reform in China since 2009. At the end of the 12th five-year plan, we conducted a series of surveys to understand BPHS implementation in Southwest China, and firstly reported implementation of health education (HE) and explore the barriers to HE delivery. Methods Mixed research methods were used to investigate achievement in and barriers to HE in Southwest China. SPSS 22.0 was used for data analysis. Results Nine hundred and eighty-nine residents were surveyed by questionnaire. 16 health care workers (HCWs) and 16 directors from 16 PHC sectors were included in the in-depth interviews. Less than 50% of residents who knew or utilized some item of HE. Age, residence, region (Chongqing or Guizhou), marital status, education, occupation, type and quality of primary health care (PHC) sectors to deliver BPHS, self-reported health and status of chronic diseases were associated with knowledge or utilization of HE. Distance to PHC sectors was associated with the knowledge of HE, gender and health insurance were associated with utilization of HE. Age, marital status, occupation region and self-reported health were associated with satisfaction regarding HE. Barriers to HE delivery included defects in HE design, weak capacity in PHC sectors to provide HE, residents' poor cooperation, lack of multi-sector cooperation, poor equipment and weak health system. Conclusions Southwest China delivered HE in all PHC sectors. However, our study underlined many barriers to equalization of HE. To address those barriers and achieve HE quality improvement, comprehensive measures to improve capacity of PHC sectors, enhance multi-sector cooperation and strengthen health information systems are all urgent needs.